Diagnoses Generated by Numerical Taxonomic Methods Applied to Standard Blood Variables - Abbott, L. A.; Mitton, J. B. (Methods of Information in Medicine, 1980)
Data taken from the blood of 262 patients diagnosed for malabsorption, elective cholecystectomy, acute cholecystitis, infectious hepatitis, liver cirrhosis, or chronic renal disease were analyzed with three numerical taxonomy (NT) methods : cluster analysis, principal components analysis, and discriminant function analysis. Principal components analysis revealed discrete clusters of patients suffering from chronic renal disease, liver cirrhosis, and infectious hepatitis, which could be displayed by NT clustering as well as by plotting, but other disease groups were poorly defined. Sharper resolution of the same disease groups was attained by discriminant function analysis.
Keywords: Computer-assisted Diagnosis; Cluster Analysis; Discriminant Function Analysis; Principal Component Analysis; Standard Blood Variables